(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The banking industry has very high impact upon the performance of the different economic sectors and the quality of people’s life in general. The banking industry has always been witnessing continuous developments andimprovements. One of the industry aspects, which went, and is still going, through a number of such developments is the “Service Mix” in terms of types, quality and range of services to be provided. Importance of this aspect stems from its noticeable impact upon satisfying market needs and enhancing the competitive position of the bank in the market place atthe same time.